Le fallacie argomentative tra logica e dialettica (Altre Modernità, 2017)
This paper is about the so-called fallacies of reasoning, that is, those arguments that seem to be compelling but don’t. It is argued that, strictly speaking, the traditional distinction between formal and pragmatic fallacies is impossible. However, another distinction, here proposed, between origin and import of fallacies turns out to be useful for classificatory purposes. The origin of a fallacy is that property on which the fallacious character of an argument ultimately depends. That property is the same in all contexts in which the fallacy can take place. By contrast, the import of a fallacy is the set of consequences that it typically has in each context. Identifying the origin of fallacies not always is a simple undertaking. In that regard, petitio principii presents special difficulties. It will be offered a detailed critique of the traditional analysis of petitio principii. This critique is aimed at showing that there are two distinct fallacies, both called petitio principii in the literature, erroneously considered as identical. It will be shown that one of these fallacies, which occurs only in the context of axiomatic proof, is a special case of non sequitur fallacy. By contrast, the other fallacy, which occurs typically in the dialectical context, derives from the fact that the credibility of a proposition cannot grow through a circular argument. A Bayesian analysis of this fact is proposed.
Keywords: Fallacies; pragmatics; petitio principia; non ampliativity; Aristotle